A manual for writers of research papers, theses, and dissertations Chicago style for students and researchers - Turabian, Kate L.; Booth, Wayne C.; Colomb, Gregory G.; Williams, Joseph M.; Bizup, Joseph 1966-; FitzGerald, William T. (Chicago The University of Chicago Press, 2018)
"This new edition of the classic reference work on writing research papers recognizes recent developments in information literacy--including finding, evaluating, and citing a wide range of digital sources--and the evolving use of software for citation management, graphics, and paper format and submission while continuing to reflect best practices for research and writing, as adapted from the most recent editions of The Craft of Research and The Chicago Manual of Style."--Provided by publisher.
Content Appendix: paper format and submission. Part III: Style. Part I: Research and writing. Source citation. On the spirit of research -- Tables and figures -- Quotations -- Abbreviations -- Numbers -- Names, special terms, and titles of works -- Spelling -- Punctuation -- Author-date style: citing specific types of sources -- Author-date style: the basic form -- Notes-bibliography style: citing specific types of sources -- Notes-bibliography style: the basic form -- General introduction to citation practices -- Presenting research in alternative forums -- Learning from comments on your paper -- Revising sentences -- Writing your final introduction and conclusion -- Revising your draft -- Presenting evidence in tables and figures -- Drafting your paper -- Planning a first draft -- Constructing your argument -- Engaging your sources -- Finding useful sources -- Defining a project: topic, question, problem, working hypothesis -- What research is and how researchers think about it --
Includes bibliographical references (pages 421-446) and index.
Keywords: Dissertations, Academic -- Handbooks, manuals, etc; Academic writing -- Handbooks, manuals, etc